Digitalization of Education: Transformation of Methods of Teaching Foreign Languages in the 21st Century (Eurasian Journal of Philology Science and Education, 2025)
The article is about how education is going digital, how well it works and on its positive and negative sides. It also evaluates the ability of digital technologies to have an impact on academic performance and motivation of the students. The article reflects on the revealing of potential of digital technologies in the educational process: in teaching foreign languages, in organization of independent work of students, and also offers some recommendations to the teachers on the process of introduction of digital technologies into the educational process. The article aims at examining the opportunities of contemporary innovative methods of foreign language teaching in the cognized context of digitalization of the educational process as well as at investigating the necessity of transformation to a creative and dynamic learning process driven by digital technologies. Digital education provides new possibilities for known learning experiences through engaging students in an interactive digital environment, and teachers through hybrids personalized learnt courses, inventive and engaging teaching strategies. Given today’s reality, the students are expected to be not just informed consumers of digital content, but effective producers of media that give voice to their ideas by integrating their learning experiences into engaging narratives and visualizations. The paper reviews the works of domestic and foreign authors explored the opportunities and some risks of digitalization of education in society. The article clearly shows the advantages and disadvantages of digital education. Since the latest and most advanced technologies are very expensive, digitalization today has both supporters and opponents. The main idea of ​​this article is to create a flexible learning environment that encourages innovation.Key words: digitalization of education, teaching foreign languages, digital technologies, teaching methods, digital transformation.